Development of an Ethnomathematics-Based Snakes and Ladders Game Media Integrating Banten Cultural Context for Teaching Number Operations in Elementary School - Arisetyawan, Andika; Fauzi, Irfan; Maulana, Farid Rizqi; Supriadi, Supriadi; Chano, Jiraporn (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop Snakes and Ladders game media for the concept of number operations by integrating the cultural context of Banten. This research employs a development method using the ADDIE model—analysis, design, development, implementation, and evaluation. The study uses a purposive sampling technique involving 20 sixth-grade students at an elementary school in Serang, Banten, selected based on considerations such as school facilities and curriculum implementation. Data were collected through number-operation tests and student reflection journals. The data were analyzed qualitatively using thematic analysis to identify themes emerging from patterns of meaning. The results show that the ethnomathematics-based Snakes and Ladders game media can enhance students’ self-efficacy and subsequently improve their understanding of number operation concepts. Furthermore, students reported increased motivation and enthusiasm during the learning process due to the engaging and enjoyable nature of the media. This study contributes to mathematics education by offering a more meaningful and enjoyable learning experience, while also reducing students’ anxiety toward mathematics. The findings further indicate that integrating cultural elements from Banten into mathematics learning can improve students’ learning outcomes.